Risk and Return Money Saving di Reksadana dan Bank Digital - Pradini, Anez Yuniar (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2023)
In the era of the industrial revolution 4.0, as it is now, digitizing the banking and financial sector is important, considering that technological disruption has touched almost all aspects of life. In the world of investment and banking, the system used is already digital-based. The financial literacy level of the Indonesian people in 2022 will increase to 49.68%. This means that people are now smarter when it comes to choosing the financial products they will use. Currently, many financial institutions offer the advantages of each product by offering quite competitive returns. As an effort to increase public literacy, this study intends to compare the two financial products, namely mutual funds in seed applications and financial products at Bank Neo Commerce (BNC). The methodology used in this research is descriptive qualitative. The results of this study state that mutual funds and money savings at BNC both have advantages in terms of features and convenience. However, both have differences in the returns offered and the risks borne. Where digital banks offer greater returns with a lower level of risk. Interestingly, investment activities have the concept of compounding interest which has the possibility of obtaining much greater returns on the condition that the investment period is extended.